1991
DOI: 10.1177/000331979104201107
|View full text |Cite
|
Sign up to set email alerts
|

Single Administration of Captopril and Combined Use with Beta-Blocker and/or Thiazide Diuretic in the Treatment of Essential Hypertension

Abstract: Thirty-four patients with essential hypertension at WHO stage I or II were divided into three groups. Group I consisted of 22 cases who displayed normal renin activity (NR) or low renin activity (LR) and who received a single administration of captopril. Group II consisted of 6 cases given beta-blockers after administration of captopril. Group III consisted of 6 cases in whom beta-blocker was replaced with thiazide diuretics after administration of captopril alone. Blood pressure decreased significantly by cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“… 30 However, and in agreement with our results, it has described that treatment with captopril and a β-blocker is not very effective and might be associated with little change in the vascular reactivity to Ang-II in SHR. 31 In addition, in patients with primary hypertension, the propranolol treatment might be associated with reduction in heart rate, 32 and captopril has shown a positive chronotropic effect by using isolated dog heart. 33 In our study and in a similar way, propranolol showed the bradycardic effect which was avoided by the combination with captopril ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“… 30 However, and in agreement with our results, it has described that treatment with captopril and a β-blocker is not very effective and might be associated with little change in the vascular reactivity to Ang-II in SHR. 31 In addition, in patients with primary hypertension, the propranolol treatment might be associated with reduction in heart rate, 32 and captopril has shown a positive chronotropic effect by using isolated dog heart. 33 In our study and in a similar way, propranolol showed the bradycardic effect which was avoided by the combination with captopril ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%